Algoritmo para cálculo e compensação da corrente capacitiva aplicado em relés diferenciais para proteção de linhas de ultra alta tensão - Giraldo, Luis Zapata (2017)
Transmission lines have different characteristics and properties that define their parameters. One of the main components that is included in the modeling is the shunt capacitance. It generates a current that becomes significant as the voltage level and line length increase. The problem is that because this capacitance is not a physical element, the current cannot be measured and must be estimated and compensated in the protection systems. This work proposes a new methodology for the estimation of the capacitive current. Moreover, it presents a description and comparison of some of the existing methods for the calculation and the compensation for Ultra High Voltage lines in the differential protection using the alpha plane. These algorithms are evaluated in a system composed of a 1000 kV transmission line built in China, which uses shunt compensation with reactors to reduce the effects of the capacitance. The analysis is done simulating operating conditions in the system such as power flow, internal faults, external and energizations. The results show that in general, the evaluated methods have adequate response. However, the proposed method in this work presents advantages in terms of availability and safety of the transmission line.